2010
DOI: 10.1161/strokeaha.109.573907
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Awareness and Treatment of Atrial Fibrillation

Abstract: Background and Purpose-Warfarin reduces stroke risk by approximately 60% in patients with atrial fibrillation (AF).Differences in awareness and treatment of AF may contribute to racial and geographic disparities in stroke mortality.The objective was to examine predictors of awareness of the diagnosis of AF and treatment with warfarin. Methods-REasons for Geographic and Racial Differences in Stroke (REGARDS) is a national, population-based, longitudinal study of 30 239 blacks and whites Ն45 years old with overs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 143 publications
(71 citation statements)
references
References 19 publications
2
69
0
Order By: Relevance
“…Despite published disparities in AF treatment between men and women 3234 and between white and black patients, 1718,35 our study did not identify a differential impact of AF by sex or race on inpatient (MedPAR) or outpatient utilization; however, the numbers of women and black participants with AF were small and were from a small number of geographic areas, so it is possible that our study was underpowered to detect a difference.…”
Section: Discussionmentioning
confidence: 60%
“…Despite published disparities in AF treatment between men and women 3234 and between white and black patients, 1718,35 our study did not identify a differential impact of AF by sex or race on inpatient (MedPAR) or outpatient utilization; however, the numbers of women and black participants with AF were small and were from a small number of geographic areas, so it is possible that our study was underpowered to detect a difference.…”
Section: Discussionmentioning
confidence: 60%
“…These studies involved analysis of administrative claims data in all patients presenting for acute care,3 prospective ascertainment of AF based on periodic ECG screening and hospitalization records,4, 5, 6, 7, 8 or examination of electronic medical records to identify clinical diagnoses of AF or ECGs showing AF 9, 10. Because none of these approaches involved long‐term continuous heart‐rhythm monitoring, their results may have reflected differences in AF symptomatology or patterns of care between white and black patients that resulted in differential ascertainment of AF12, 13 rather than true differences in the burden of AF. A prospective study assessed racial differences in AF detection using pacemakers or implanted defibrillators, but this study included a small number of black patients and was able to adjust for a limited number of potentially confounding factors 11.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, studies consistently report that black patients have lower rates of atrial fibrillation (AF)—one of the strongest risk factors for stroke2—than white patients 3, 4, 5, 6, 7, 8, 9, 10, 11. It is unclear whether the lower reported rate of AF in black persons represents a truly lower burden of AF or more frequent underdiagnosis of this often paroxysmal dysrhythmia in black persons 12, 13. Better understanding of the true relative burden of AF in black persons may shed light on reasons for racial disparities in stroke rates that cannot be entirely accounted for by differences in demographic and socioeconomic characteristics or the prevalence of established stroke risk factors 14.…”
Section: Introductionmentioning
confidence: 99%
“…In the REGARDS study, our research group has previously shown that blacks and women are less likely to be aware of having AF or to be treated with warfarin. 24 The excess risk of MI coupled with the tendency to under-treat AF may magnify the risk of poor outcomes in these 2 groups.In a stratified analysis by warfarin use, the risk of MI associated with AF was lower in warfarin users than in nonusers, suggesting an effect modification by warfarin use. This accords with previous reports showing that warfarin might provide a protective effect against MI after acute coronary syndromes 25 and in patients with AF who are prescribed anticoagulation for stroke prevention.…”
mentioning
confidence: 99%